Tnni1b-ECR183-d2, an 87 bp cardiac enhancer of zebrafish - Zhang,Yawen; Wang,Feng; Wu,Fang; Wang,Youhua; Wang,Xu; Gui,Yonghao; Li,Qiang (PeerJ, 2020)
Background Several heart malformations are associated with mutations in the regulatory regions of cardiac genes. Troponin I type 1b (tnni1b) is important for the formation of the atrioventricular canal in zebrafish hearts; however, the regulation of tnni1b is poorly understand. We aimed to identify a small but functional enhancer that is distal to tnni1b. Methods Evolutionary Conserved Region (ECR) Browser was used to analyze the 219 kb zebrafish and human genomes covering the tnni1b gene as well as the 100 kb regions upstream and downstream of tnni1b. Putative transcription factor binding sites (TFBSs) were analyzed using JASPAR and PROMO, and the enhancer activity was identified using zebrafish embryos and the luciferase reporter assay. A correlation analysis between the enhancer and transcription factors (TFs) was performed via TF overexpression and TFBS mutation experiments and the electrophoretic mobility shift assay (EMSA). To analyze the conservation between zebrafish and human enhancers, human DNA fragments were functionally verified. Images were captured and analyzed by fluorescence microscopy or confocal microscopy. Results Combined with comparative analysis and functional validation, we identified a 183 bp ECR (termed tnni1b-ECR183) that was located approximately 84 kb upstream of tnni1b that had the heart-specific enhancer activity in zebrafish. TFBS analysis and the enhancer activity detection assay data showed that the 87 bp core region (termed tnni1b-ECR183-d2) was capable of driving specific GFP expression near the atrioventricular junction and increased luciferase expression in HEK293 and HL1 cell lines. The GFP pattern in zebrafish embryos was similar to the expression profiles of tnni1b. A correlation analysis showed that the enhancer activity of tnni1b-ECR183-d2 was increased when NKX2.5 (p = 0.0006) or JUN (p < 0.0001) was overexpressed and was decreased when the TFBSs of NKX2.5 (p < 0.0001) or JUN (p = 0.0018) were mutated. In addition, DNA-protein interactions were not observed between these TFs and tnni1b-ECR183-d2 in the EMSA experiment. The conservation analysis showed that tnni1b-ECR183-h179 (aligned from tnni1b-ECR183) drove GFP expression in the heart and skeletal muscles and increased the luciferase expression after NKX2.5 (p < 0.0001), JUN (p < 0.0001) or ETS1 (p < 0.0001) was overexpressed. Interestingly, the truncated fragment tnni1b-ECR183-h84 mainly drove GFP expression in the skeletal muscles of zebrafish and the enhancer activity decreased when NKX2.5 (p = 0.0028), ETS1 (p = 0.0001) or GATA4 (p < 0.0001) was overexpressed. Conclusions An 87 bp cardiac-specific enhancer located 84 kb upstream of tnni1b in zebrafish was positively correlated with NKX2.5 or JUN. The zebrafish and human enhancers in this study target different tissues. The GFP expression mediated by tnni1b-ECR183-d2 is a valuable tool for marking the domain around the atrioventricular junction.
Keywords: Evolutionary conserved region; Tnni1b; Cis-regulators; Transgenic zebrafish line; Transcription factor